How we can disrupt ecosystem of urban lakes– pollutants of bottom sediment in two shallow water bodies - Jolanta Katarzyna Grochowska; Renata Tandyrak; Renata Augustyniak; Michał Łopata; Dariusz Popielarczyk; Tomasz Templin (Archives of Environmental Protection, 2021)
The research covered two lakes: Karczemne and Domowe Małe, which served as receivers for rainwater and municipal or industrial sewage. The sediment cores were obtained using a Kajak tube sampler. Analyses of HM, PAH and PCB were done by the AAS, ICP-AES and GC MS methods. OM, SiO2, TH, Ca, Mg, CO2, Fe, Al, Mn, TN and TP were measured. The research showed that the sediments of Lake Karczemne, into which the untreated municipal sewage was discharged, are characterized by a high content of P. It was found that the sediments accumulate toxins, OM and pollutants characteristic for various industries. Karczemne Lake which collected municipal and industrial wastewater, contained a high content of Pb, Cu and PAH in the sediments, and Domowe Małe Lake, receiving stormwater, contained high concentrations of PAH. Research has shown that one of the most important tools for selecting an appropriate method of lake restoration is the analysis of the spatial distribution of pollutants in the bottom sediments. Thanks to such an analysis of the composition of the bottom sediments and the correlation between the components of the sediments and their sorption properties, the restoration of the Karczemne Lake using the Ripl method was planned and the possibility of restoration of the Domowe Małe Lake in this way was eliminated.